2006
DOI: 10.1212/01.wnl.0000190257.55434.ab
|View full text |Cite
|
Sign up to set email alerts
|

Successful bilateral pallidal stimulation for Meige syndrome and spasmodic torticollis

Abstract: We describe a 65-year-old man who had medically refractory craniofacial dystonia with blepharospasm (Meige syndrome) and spasmodic torticollis (video, part 1). Initial botulinum toxin injections had been discontinued because of adverse side effects and a loss of efficacy. After informed consent, the patient received bilateral pallidal electrodes for deep brain stimulation (DBS). With neurostimulation, symptoms nearly resolved (video, part 2), with sustained efficacy at 4-month follow-up. Our case is in line wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 2 publications
3
19
0
1
Order By: Relevance
“…Since Vercueil and coworkers 3 first reported their results of bilateral GPi DBS in a patient with Meige syndrome, several studies have shown that segmental dystonia responds to GPi DBS. 2,3,6,9,11,13,[18][19][20][21][22][23][24][25][29][30][31] The reports on Meige syndrome and its response to DBS are primarily single cases, aside from the excellent report by Ostrem and colleagues 25 ( Table 3). The follow-up time frame has been somewhat limited in most reports, except the cases of Loher et al 21 at 7 years, Hebb et al 11 at 5 years, and Capelle and associates 6 at 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since Vercueil and coworkers 3 first reported their results of bilateral GPi DBS in a patient with Meige syndrome, several studies have shown that segmental dystonia responds to GPi DBS. 2,3,6,9,11,13,[18][19][20][21][22][23][24][25][29][30][31] The reports on Meige syndrome and its response to DBS are primarily single cases, aside from the excellent report by Ostrem and colleagues 25 ( Table 3). The follow-up time frame has been somewhat limited in most reports, except the cases of Loher et al 21 at 7 years, Hebb et al 11 at 5 years, and Capelle and associates 6 at 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…15 Meige syndrome has become the most common eponym current used in the literature. 2,3,6,9,11,13,21,23,24,27,30 Meige syndrome is characterized by blepharospasm, cervical dystonia, and facial oromandibular dystonia. The underlying cause of Meige syndrome is unknown, but most investigators consider it a variant of idiopathic torsion dystonia.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In such cases a treatment option can be stereotactic surgical ablation or deep brain stimulation (DBS) of the globus pallidus internus (GPi). A beneficial effect of GPi-DBS has been reported on the forms of MS associated with anterocollis and segmental axial dystonia [7] , with multifocal dystonia [8] , with segmental axial dystonia after ineffective bilateral thalamotomy [9] , with spasmodic torticollis [10,11] and with dystonic tremor [12] . There are only few reports on successful surgical treatment of isolated MS [13,14] .…”
Section: Introductionmentioning
confidence: 99%